Does surgically resected small‐cell lung cancer without lymph node involvement benefit from prophylactic cranial irradiation? - Yuqing Lou; Runbo Zhong; Jianlin Xu; Rong Qiao; Jiajun Teng; Yanwei Zhang; Xueyan Zhang; Tianqing Chu; Hua Zhong; Baohui Han (Thoracic Cancer)
Abstract Background It has previously been demonstrated that surgically resected small‐cell lung cancer (SCLC) patients could benefit from prophylactic cranial irradiation (PCI). However, PCI in patients without lymph node involvement remains controversial. This study includes a larger sample size to evaluate the benefit of PCI therapy in this specific population. Methods The records of surgically resected SCLC patients without lymph node involvement (N0M0) in Shanghai Chest Hospital were retrospectively reviewed. Results Between January 2006 and May 2017, a total of 146 cases of surgically resected SCLC without lymph node involvement were included. A total of 46 patients received PCI therapy and 100 patients received no therapy. During the observation period, 12.0% (12/100) of the patients who did not receive PCI therapy developed brain metastases while 10.9% (5/46) of patients who received PCI therapy developed brain metastases. With regard to time to recurrence, no significant difference was observed among the groups (P = 0.798). Moreover, there was no significant difference in either the overall survival benefit (hazard ratio [HR] = 0.84, 95% confidence interval [CI]: 0.49–1.45, P = 0.532) or disease‐free survival rate (HR = 0.95, 95% CI: 0.52–1.75, P = 0.864). Conclusions The evidence obtained does not support PCI therapy in the management of surgically resected SCLC with no lymph node involvement. Key points Prophylactic cranial irradiation (PCI) remains controversial for resected small‐cell lung cancer (SCLC) without lymph node involvement. In this study, the results indicated that PCI does not reduce the risk of cerebral recurrence of resected p‐T1‐2N0M0 SCLC. This is the largest sample size study focused on PCI in resected p‐T1‐2N0M0 SCLC. Future revised versions of the guidelines should address this issue.